(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Strategic planning is an important management approach that increases the efficiency of the organisation, service delivery and competitiveness especially in public institutions operating in dynamic settings. Strategic plans have been broadly embraced by public universities, yet many still find it difficult to convert strategic objectives into better organizational performance. Existing studies have mostly focused on strategic planning as a general management technique with little attention paid to the integrated impact of implementation elements such as resource allocation, performance rating systems, and organisational culture notably in the context of Kenyan public universities. Hence, this study sought to investigate the influence of strategic planning implementation on organizational performance at Rongo University, Kenya by focusing on resource allocation, performance appraisal systems and organizational culture. The study was based on an Organizational Culture Theory which states that shared values, norms and attitudes influence organizational behaviour and effectiveness. The study used a descriptive case study research approach. The study population included administrative staff, heads of departments, directors, deans and members of the university management board. Data were obtained through structured questionnaires from primary and secondary sources and analyzed using descriptive statistics and multiple regression analysis with the use of SPSS software.The results demonstrated that a considerable positive relationship exists between strategic planning execution and organizations’ performance. There is efficient allocation of resources that has boosted the performance through enough financial support, efficient monitoring and auditing systems, optimal utilization of physical resources, and availability of qualified individuals. However, successful execution has been hampered by poor adoption of information technology. Clear procedures, supportive policies and participatory evaluation processes in performance appraisal systems boosted organizational performance, but lack of regular review sessions hindered the utilization of appraisal results for staff development and continuous improvement. The study also revealed a considerable effect of the organizational culture on the implementation of strategic planning and on the efficacy of the institution. The implementation was also facilitated by employee participation in decision-making, reporting structures, delegation of responsibilities and common organisational principles. Inflexible hierarchical structures impeded decision-making and compromised flexibility. Regression results indicated that organizational culture had a substantial beneficial effect on organizational performance (β = 0.334, p = 0.002). The study shows that the successful implementation of the strategic plans has a considerable positive impact on the performance of public universities. It recommends the strengthening of resource allocation mechanisms, enhancement of information technology adoption, improvement of performance appraisal practices, promotion of participatory management and the fostering of flexible organizational structures to enhance strategic plan implementation and institutional performance.